Incidence of Argas miniatus Koch in Matosinhos, Minas Gerais - Loureiro, Milgar Camargos; Junqueira Neto, Desidério (Pesquisa Agropecuaria Brasileira, 2024)
A survey was made in Matosinhos town, State of Minas Gerais, Brazil, to study the intensity of infestation of Argas miniatus Koch, Acarina, Argasidae. Fourty properties, in which chickens were raised on a non-commercial basis were found to be infested by this parasite at the range of 46.3%. Only three owners knew the parasite while only one knew to control it.